Perancangan Sistem Informasi Point of Sale Berbasis Website pada Toko Azam Grosir dengan Metode Waterfall - Herdiansyah, Aditya Tri; Pratama, Arnold Agusti; Octavia, Indriyani; Baehaqi, Reza Anwar Sidiq; Saifudin, Aries; Desyani, Teti (Jurnal Informatika Universitas Pamulang, 2021)
The sales process at the Azam Wholesale Store is still done conventionally with manual recording. The manual recording system is less efficient because it requires a lot of books and orders that must be recorded into the books manually. This condition also causes errors in entering/recording sales data. Making reports takes a long time because they have to find and collect the necessary data from the notes in the book. In this study, we proposed to develop a POS (Point of Sale) application to solve existing problems so that store work activities can run smoothly. The method used in this POS system is the Waterfall method. The Waterfall method is a method used to develop software sequentially (such as a waterfall) that goes through several stages, namely planning, design, implementation, and testing. The application developed shows that the Point of Sale (POS) system can facilitate Toko Azam Grosir in recording, calculating, making documents and sales information to manage and recapitulate sales reports.